Foam-producing dispersion liquid as well as preparation method and application thereof
The foam-producing dispersion prepared by using polyacrylamide, weathered coal and betaine type surfactant was solved, and the foam stability and long half-life of the foam in a high-salt environment were achieved, and the reservoir displacement effect was improved.
Patent Information
- Application Number
- CN202311592789.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-27
- Publication Date
- 2025-05-27
- Estimated Expiration
- 2043-11-27
AI Technical Summary
It is difficult to effectively develop high-mineralization reservoirs, especially slot oil reservoirs, which have problems such as poor foam stability, early gravity separation, and serious flow traversal.
A bubble production dispersion liquid is used, and its raw materials include polyacrylamide, weathered coal, betaine type surfactant and water. Through specific mixing steps and stirring conditions, a bubble production dispersion liquid with excellent bubble production and bubble stabilization effects is prepared.
The bubble production dispersion can maintain the stability of the foam in a high-salt environment, extend the half-life of the foam, and is suitable for high-mineralization slot hole reservoirs, significantly improving the reservoir's displacement effect.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of oil and gas field development engineering, and particularly to a foam-producing dispersion liquid, a preparation method thereof, and an application thereof. Background Art
[0002] In recent years, displacement and profile control systems for reservoirs with low temperature (<80°C) and medium-low salinity (<2.0×10 4 mg / L) have developed rapidly both at home and abroad, and the on-site application effect is good. However, the development of displacement and profile control systems under reservoir conditions with high salinity, especially above 2.0×10 4 mg / L, is relatively slow. On the one hand, using a single salt-tolerant surfactant, there is an upper limit for a single system, and there is no potential for deep exploration. On the other hand, for fractured-vuggy reservoirs, the reservoir space is too large, resulting in a weakened foam shear regeneration ability. The foam stability is too poor, leading to premature gravity segregation and serious channeling phenomena. Therefore, there are many challenges in the exploitation of fractured-vuggy reservoirs. Summary of the Invention
[0003] One aspect of the present invention provides a foam-producing dispersion liquid, the raw materials of which include polyacrylamide, weathered coal, betaine-type surfactant, and water.
[0004] In a specific embodiment, the polyacrylamide is non-ionic polyacrylamide.
[0005] In a specific embodiment, the relative molecular weight of the non-ionic polyacrylamide is 4 million to 6 million.
[0006] In a specific embodiment, the carbon content of the weathered coal is 60 wt% to 65 wt%, and the ash content is 15 wt% to 22 wt%. For example, the weathering duration of the weathered coal is 3 months to 4 months. Among them, weathering can be erosion by the atmosphere and sunlight.
[0007] In a specific embodiment, the particle size of the weathered coal is 25 μm to 75 μm.
[0008] In a specific embodiment, the betaine-type surfactant is at least one of hydroxysulfobetaine, coconut oil amide propyl betaine, and lauroyl propyl betaine.
[0009] In a specific embodiment, taking the mass of water as 100%, the dosage of the polyacrylamide is 0.5% to 0.8%, the dosage of the weathered coal is 5% to 15%, and the dosage of the betaine-type surfactant is 0.3% to 0.7%.
[0010] Another aspect of the present invention provides a method for preparing the foam-producing dispersion liquid as described in any one of the first aspect of the present invention, which includes the following steps:
[0011] 1-1) Mix polyacrylamide with water to obtain an aqueous polyacrylamide solution;
[0012] 2-1) Mix weathered coal with the aqueous polyacrylamide solution to obtain a dispersion;
[0013] 3-1) Mix the dispersion with a betaine surfactant to obtain the foaming dispersion.
[0014] Alternatively, the second aspect of the present invention provides a method for preparing the foaming dispersion as described in any one of the first aspect of the present invention, which includes the following steps:
[0015] 1-2) Mix polyacrylamide with water to obtain an aqueous polyacrylamide solution;
[0016] 2-2) Mix a betaine surfactant with the aqueous polyacrylamide solution to obtain an aqueous polyacrylamide-betaine solution;
[0017] 3-2) Mix the aqueous polyacrylamide-betaine solution with weathered coal to obtain the foaming dispersion.
[0018] In a specific embodiment, in step 1-1) or step 1-2), stir at 600 to 800 rpm for 30 to 45 min to mix evenly.
[0019] In a specific embodiment, in step 2-1) or step 3-2), first stir at 800 to 1000 rpm for 20 to 30 min to mix evenly, and then perform ultrasonic dispersion for 5 to 10 min.
[0020] In a specific embodiment, in step 3-1) or step 2-2), stir at 400 to 600 rpm for 5 to 10 min to mix.
[0021] The third aspect of the present invention provides the application of the foaming dispersion as described in any one of the first aspect of the present invention or the foaming dispersion prepared by the method as described in any one of the second aspect of the present invention in displacing the oil stored in the fractures and / or within the fracture-cavities of a high salinity fracture-cavity reservoir.
[0022] In a specific embodiment, the application is in displacing the oil stored in the fractures and / or within the fracture-cavities of a high salinity salt rock formation and / or a fracture-cavity reservoir with high salinity caused by sedimentation.
[0023] In a specific embodiment, the application is in displacing the oil stored in the fractures and / or within the fracture-cavities of a shallow layer of a high salinity marine sedimentary rock formation and / or a fracture-cavity reservoir with high temperature and high salinity caused by marine sedimentation.
[0024] In a specific embodiment, the upper limit of the salinity is 21×10 4 mg / L.
[0025] In a specific embodiment, the upper limit value of the high temperature is 150 °C.
[0026] Advantages of the present invention:
[0027] The foam-producing dispersion of the present invention has good foaming and foam-stabilizing effects. By using weathered coal and the synergistic effect among components, the stability of the foam is greatly improved, and the half-life of the foam is prolonged.
[0028] The foam-producing dispersion of the present invention can be applied to high-salinity fracture-vuggy reservoirs, can tolerate a high salinity of 21×10 4 mg / L, can tolerate calcium ions of 1.4×10 4 mg / L, and can tolerate magnesium ions of 0.2×10 4 mg / L.
[0029] The foam-producing dispersion of the present invention can be applied to both normal temperature and high temperature, and has a wide application temperature range.
[0030] The raw material weathered coal particles used in the present invention belong to waste resources in the mine field. Polyacrylamide is inexpensive and widely used in the petrochemical field. While improving the foam stability, this system greatly reduces the production cost. Specific embodiments
[0031] The present invention will be further described below in conjunction with embodiments. However, the embodiments of the present invention are only exemplary descriptions, and in no case do they constitute a limitation to the present invention.
[0032] Example 1
[0033] A salt-tolerant foam-producing dispersion, which comprises raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35-μm weathered coal (with a carbon content of 65 wt%, an ash content of 15%, and formed by weathering for 3 months by the erosion of the atmosphere and sunlight), 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0034] A preparation method of the salt-tolerant foam-producing dispersion, the specific steps are as follows:
[0035] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ions are 1.4×10 4 mg / L, and magnesium ions are 0.2×10 4In (mg / L), stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0036] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves of 20 kHz for 5 min to obtain a dispersion.
[0037] (3) Add 0.5 part by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion.
[0038] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After stirring is completed, obtain a foam system. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0039] Example 2
[0040] A salt-tolerant foam-producing dispersion, which comprises raw materials: 0.8 part by mass of a non-ionic polyacrylamide with a relative molecular weight of 5 million, 15 parts by mass of 35-μm weathered coal (carbon content is 65 wt%, ash content is 15 wt%, formed by weathering for 3 months by the erosion of the atmosphere and sunlight), 0.7 part by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0041] A preparation method of the salt-tolerant foam-producing dispersion, and the specific steps are as follows:
[0042] (1) Add 0.8 part by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, magnesium ion is 0.2×10 4 mg / L), stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0043] (2) Add 15 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves of 20 kHz for 5 min to obtain a dispersion.
[0044] (3) Add 0.7 part by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion.
[0045] Add the foam-producing dispersion into a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0046] Example 3
[0047] A salt-tolerant foam-producing dispersion, which comprises raw materials: 0.5 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 5 parts by mass of weathered coal (with a carbon content of 65 wt%, an ash content of 15 wt%, formed by being eroded by the atmosphere and sunlight for 3 months) with a particle size of 35 μm, 0.3 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0048] A preparation method of the salt-tolerant foam-producing dispersion, and the specific steps are as follows:
[0049] (1) Add 0.5 parts by mass of polyacrylamide into 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, and magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0050] (2) Add 5 parts by mass of weathered coal particles into the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0051] (3) Add 0.3 parts by mass of hydroxysulfobetaine into the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly to obtain a foam-producing dispersion.
[0052] Add the foam-producing dispersion into a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0053] Example 4
[0054] The difference from Example 1 is only that the relative molecular weight of the non-ionic polyacrylamide is 4 million.
[0055] Salt-tolerant foaming dispersion liquid, which comprises raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 4 million, 10 parts by mass of 35-μm weathered coal (carbon content is 65 wt%, ash content is 15 wt%, formed by being weathered by the atmosphere and sunlight for 3 months), 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0056] Preparation method of the salt-tolerant foaming dispersion liquid, the specific steps are as follows:
[0057] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0058] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves of 20 kHz for 5 min to obtain a dispersion liquid.
[0059] (3) Add 0.5 parts by mass of hydroxysulfobetaine to the dispersion liquid. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly to obtain a foaming dispersion liquid.
[0060] Add the foaming dispersion liquid to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0061] Example 5
[0062] The difference from Example 1 is only that the relative molecular weight of the non-ionic polyacrylamide is 6 million.
[0063] Salt-tolerant foaming dispersion liquid, which comprises raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 6 million, 10 parts by mass of 35-μm weathered coal (carbon content is 65 wt%, ash content is 15 wt%, formed by being weathered by the atmosphere and sunlight for 3 months), 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0064] Preparation method of the salt-tolerant foaming dispersion liquid, the specific steps are as follows:
[0065] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4Simulated formation water with a salinity of 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4 mg / L), and uniformly stirred at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0066] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0067] (3) Add 0.5 part by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion.
[0068] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, start the stopwatch at the same time, and record its foaming volume and drainage half-life. The results are shown in Table 1.
[0069] Example 6
[0070] The difference from Example 1 is only that the particle size of the weathered coal is 25 μm.
[0071] Salt-tolerant foam-producing dispersion, which comprises raw materials: 0.6 part by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 25-μm weathered coal (carbon content is 65 wt%, ash content is 15 wt%, formed by weathering for 3 months by the erosion of the atmosphere and sunlight), 0.5 part by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0072] Preparation method of the salt-tolerant foam-producing dispersion, and the specific steps are as follows:
[0073] (1) Add 0.6 part by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4 mg / L), and uniformly stir at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0074] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0075] (3) Add 0.5 parts by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly, obtaining a foam-producing dispersion.
[0076] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start the stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0077] Example 7
[0078] The difference from Example 1 is only that the particle size of the weathered coal is 75 μm.
[0079] Salt-tolerant foam-producing dispersion, which comprises raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 75-μm weathered coal (with a carbon content of 65 wt% and an ash content of 15 wt%, formed by being eroded by the atmosphere and sunlight for 3 months), 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0080] Preparation method of the salt-tolerant foam-producing dispersion, the specific steps are as follows:
[0081] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, and magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0082] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0083] (3) Add 0.5 parts by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly, obtaining a foam-producing dispersion.
[0084] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start the stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0085] Example 8
[0086] It is different from Example 1 only in that the hydroxysulfobetaine is replaced with cocoamidopropyl betaine.
[0087] A salt-tolerant foaming dispersion, which comprises raw materials: 0.6 parts by mass of a non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35-μm weathered coal (with a carbon content of 65 wt% and an ash content of 15 wt%, formed by weathering by the atmosphere and sunlight for 3 months), 0.5 parts by mass of cocoamidopropyl betaine, and 100 parts by mass of mineralized water.
[0088] A method for preparing a salt-tolerant foaming dispersion, the specific steps are as follows:
[0089] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0090] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves of 20 kHz for 5 min to obtain a dispersion.
[0091] (3) Add 0.5 parts by mass of cocoamidopropyl betaine to the dispersion, and in order to prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly to obtain a foaming dispersion.
[0092] Add the foaming dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0093] Example 9
[0094] It is different from Example 1 only in that the hydroxysulfobetaine is replaced with lauroyl propyl betaine.
[0095] A salt-tolerant foaming dispersion, which comprises raw materials: 0.6 parts by mass of a non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35-μm weathered coal (with a carbon content of 65 wt% and an ash content of 15 wt%, formed by weathering by the atmosphere and sunlight for 3 months), 0.5 parts by mass of lauroyl propyl betaine, and 100 parts by mass of mineralized water.
[0096] A method for preparing a salt-tolerant foaming dispersion, the specific steps are as follows:
[0097] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0098] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0099] (3) Add 0.5 parts by mass of lauroyl propyl betaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion.
[0100] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After stirring is completed, obtain a foam system. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0101] Example 10
[0102] The difference from Example 1 lies in the different weathering durations, with both the carbon content and ash content being different.
[0103] Salt-tolerant foam-producing dispersion, which includes raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35-μm weathered coal (carbon content is 60 wt%, ash content is 22 wt%, formed by weathering under the erosion of the atmosphere and sunlight for 4 months), 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0104] Preparation method of the salt-tolerant foam-producing dispersion, and the specific steps are as follows:
[0105] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0106] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion liquid.
[0107] (3) Add 0.5 part by mass of hydroxysulfobetaine to the dispersion liquid. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion liquid.
[0108] Add the foam-producing dispersion liquid to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, obtain a foam system. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0109] Example 11
[0110] The difference from Example 1 lies in the different mixing conditions in steps (2) to (5).
[0111] Salt-tolerant foam-producing dispersion liquid, which includes raw materials: 0.6 part by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35-μm weathered coal (carbon content is 65 wt%, ash content is 15%, formed by weathering for 3 months by the erosion of the atmosphere and sunlight), 0.5 part by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0112] Preparation method of the salt-tolerant foam-producing dispersion liquid, the specific steps are as follows:
[0113] (1) Add 0.6 part by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, magnesium ion is 0.2×10 4 mg / L), stir evenly at 1000 rpm, and the stirring time is 30 min to obtain an aqueous polyacrylamide solution.
[0114] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 1000 rpm for 20 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 10 min to obtain a dispersion liquid.
[0115] (3) Add 0.5 part by mass of hydroxysulfobetaine to the dispersion liquid. To prevent foaming during stirring, stir at a low speed of 600 rpm for 10 min to mix evenly and obtain a foam-producing dispersion liquid.
[0116] The foaming dispersion was added to a foam stirrer and stirred at a high speed of 8000 rpm for 3 min. After stirring, a foam system was obtained. The foam system was poured into a graduated cylinder, and at the same time, a stopwatch was started to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0117] Comparative Example 1
[0118] The difference from Example 1 is only that the non-ionic polyacrylamide is replaced by polyethylene oxide.
[0119] The foaming dispersion includes raw materials: 0.6 parts by mass of polyethylene oxide with a relative molecular weight of 5 million, 10 parts by mass of weathered coal (carbon content 65 wt%, ash content 15 wt%, formed by weathering for 3 months by the erosion of the atmosphere and sunlight) with a particle size of 35 μm, 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0120] The preparation method of the foaming dispersion is as follows:
[0121] (1) 0.6 parts by mass of polyethylene oxide was added to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4 mg / L), and uniformly stirred at 600 rpm for 45 min to obtain an aqueous polyethylene oxide solution.
[0122] (2) 10 parts by mass of weathered coal particles were added to the aqueous polyethylene oxide solution, and stirred at 800 rpm for 30 min to mix evenly, and then dispersed under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0123] (3) 0.5 parts by mass of hydroxysulfobetaine was added to the dispersion. To prevent foaming during stirring, it was stirred at a low speed of 400 rpm for 5 min to mix evenly, and a foaming dispersion was obtained.
[0124] The foaming dispersion was added to a foam stirrer and stirred at a high speed of 8000 rpm for 3 min. After stirring, a foam system was obtained. The foam system was poured into a graduated cylinder, and at the same time, a stopwatch was started to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0125] Comparative Example 2
[0126] The difference from Example 1 is that the weathered coal particles are replaced by fly ash particles.
[0127] Foaming dispersion liquid, which includes raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35μm fly ash particles, 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0128] Preparation method of foaming dispersion liquid, the specific steps are as follows:
[0129] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 minutes to obtain an aqueous polyacrylamide solution.
[0130] (2) Add 10 parts by mass of fly ash particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 minutes to mix evenly, and then disperse under ultrasonic wave of 20 kHz for 5 minutes to obtain a dispersion liquid.
[0131] (3) Add 0.5 parts by mass of hydroxysulfobetaine to the dispersion liquid. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 minutes to mix evenly to obtain a foaming dispersion liquid.
[0132] Add the foaming dispersion liquid to a foam stirrer and stir at a high speed of 8000 rpm for 3 minutes. At the same time, to prevent the foaming effect from decreasing due to excessive viscosity, nitrogen is introduced throughout the stirring process. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0133] Comparative Example 3
[0134] The difference from Example 1 is only that weathered coal is replaced by rubber particles.
[0135] Foaming dispersion liquid, which includes raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35μm rubber particles, 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0136] Preparation method of foaming dispersion liquid, the specific steps are as follows:
[0137] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ion is 1.4×10 4 mg / L and magnesium ion is 0.2×10 4In (mg / L), stir evenly at 600 rpm for 45 min to obtain an aqueous polyacrylamide solution.
[0138] (2) Add 10 parts by mass of rubber particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion.
[0139] (3) Add 0.5 part by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion.
[0140] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0141] Comparative Example 4
[0142] The difference from Example 1 is only that the weathering time of the weathered coal is different, so the carbon content and ash content are different. Specifically, the carbon content is 55 wt% and the ash content is 25 wt%. It is formed by weathering by the atmosphere and sunlight for 5 months.
[0143] A foam-producing dispersion, which includes raw materials: 0.6 part by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35 μm weathered coal, 0.5 part by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0144] The specific steps of the preparation method of the foam-producing dispersion are as follows:
[0145] (1) Add 0.6 part by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, and magnesium ion is 0.2×10 4 mg / L), stir at a high speed of 600 rpm for 45 min to obtain an aqueous polyacrylamide solution;
[0146] (2) Add 10 parts by mass of weathered coal particles to the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion;
[0147] (3) Add 0.5 part by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly and obtain a foam-producing dispersion.
[0148] Add the foam-producing dispersion into a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0149] Comparative Example 5
[0150] The difference from Example 1 is only that the weathering duration of the weathered coal is different, so the carbon content and ash content are different. Specifically, the carbon content is 70 wt%, the ash content is 10 wt%, and it is formed by weathering for 2 months by the erosion of the atmosphere and sunlight.
[0151] The foam-producing dispersion includes raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 10 parts by mass of 35-μm weathered coal, 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0152] The specific steps of the preparation method of the foam-producing dispersion are as follows:
[0153] (1) Add 0.6 parts by mass of polyacrylamide into 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (wherein, calcium ion is 1.4×10 4 mg / L, magnesium ion is 0.2×10 4 mg / L), and stir at a high speed of 600 rpm for 45 min to obtain an aqueous polyacrylamide solution;
[0154] (2) Add 10 parts by mass of weathered coal particles into the aqueous polyacrylamide solution, stir at 800 rpm for 30 min to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 min to obtain a dispersion;
[0155] (3) Add 0.5 parts by mass of hydroxysulfobetaine into the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 min to mix evenly to obtain the foam-producing dispersion.
[0156] Add the foam-producing dispersion into a foam stirrer and stir at a high speed of 8000 rpm for 3 min. After the stirring is completed, a foam system is obtained. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0157] Comparative Example 6
[0158] The foam-producing dispersion includes raw materials: 0.6 parts by mass of non-ionic polyacrylamide with a relative molecular weight of 5 million, 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0159] The preparation method of the foam-producing dispersion, the specific steps are as follows:
[0160] (1) Add 0.6 parts by mass of polyacrylamide to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ions are 1.4×10 4 mg / L and magnesium ions are 0.2×10 4 mg / L), and stir evenly at 600 rpm for 45 minutes to obtain an aqueous polyacrylamide solution.
[0161] (2) Add 0.5 parts by mass of hydroxysulfobetaine to the aqueous polyacrylamide solution. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 minutes to mix evenly and obtain a foam-producing dispersion.
[0162] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 minutes. After stirring is completed, obtain a foam system. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0163] Comparative Example 7
[0164] A foam-producing dispersion, which includes the following raw materials: 10 parts by mass of weathered coal with a particle size of 35 μm (carbon content is 65 wt%, ash content is 15%, formed by weathering for 3 months by the erosion of the atmosphere and sunlight), 0.5 parts by mass of hydroxysulfobetaine, and 100 parts by mass of mineralized water.
[0165] A method for preparing the foam-producing dispersion, the specific steps are as follows:
[0166] (1) Add 10 parts by mass of weathered coal particles to 100 parts by mass of simulated formation water with a salinity of 21×10 4 mg / L (where calcium ions are 1.4×10 4 mg / L and magnesium ions are 0.2×10 4 mg / L), stir at 800 rpm for 30 minutes to mix evenly, and then disperse under ultrasonic waves at 20 kHz for 5 minutes to obtain a dispersion.
[0167] (2) Add 0.5 parts by mass of hydroxysulfobetaine to the dispersion. To prevent foaming during stirring, stir at a low speed of 400 rpm for 5 minutes to mix evenly and obtain a foam-producing dispersion.
[0168] Add the foam-producing dispersion to a foam stirrer and stir at a high speed of 8000 rpm for 3 minutes. After stirring is completed, obtain a foam system. Pour the foam system into a graduated cylinder, and at the same time, start a stopwatch to record its foaming volume and drainage half-life. The results are shown in Table 1.
[0169] Table 1
[0170] Example Foaming volume / ml Half-life of bleeding liquid / min Example 1 310 92 Example 2 350 136 Example 3 325 72 Example 4 345 112 Example 5 310 110 Example 6 325 125 Example 7 300 61 Example 8 315 81 Example 9 310 60 Example 10 305 80 Example 11 310 93 Comparative Example 1 270 42 Comparative Example 2 325 51 Comparative Example 3 245 48 Comparative Example 4 295 50 Comparative Example 5 265 55 Comparative Example 6 275 45 Comparative Example 7 305 35
[0171] As can be seen from Table 1 above, the foam-producing dispersion provided by the present invention has excellent foaming performance and half-life, and can meet the requirements of complex oil and gas fields, especially high salinity, for high foam stability.
[0172] Although the present invention has been described with reference to specific embodiments, those skilled in the art should understand that various changes can be made without departing from the true spirit and scope of the present invention. In addition, various changes can be made to the subject matter, spirit and scope of the present invention to adapt to specific situations, materials, material compositions and methods. All such changes are included within the scope of the claims of the present invention.
Claims
1. A foaming dispersion, the raw materials of which include polyacrylamide, weathered coal, betaine-type surfactant and water.
2. The foaming dispersion according to claim 1, characterized in that the polyacrylamide is non-ionic polyacrylamide; Preferably, the relative molecular weight of the non-ionic polyacrylamide is 4 million to 6 million.
3. The foaming dispersion according to claim 1, characterized in that the carbon content of the weathered coal is 60wt% to 65wt%, and the ash content is 15wt% to 22wt%; Preferably, the particle size of the weathered coal is 25μm to 75μm.
4. The foaming dispersion according to claim 1, characterized in that the betaine-type surfactant is at least one of hydroxysulfobetaine, coconut oil amide propyl betaine and lauroyl propyl betaine.
5. The foaming dispersion according to claim 1, characterized in that taking the mass of water as 100%, the dosage of the polyacrylamide is 0.5% to 0.8%, the dosage of the weathered coal is 5% to 15%, and the dosage of the betaine-type surfactant is 0.3% to 0.7%.
6. A method for preparing the foaming dispersion according to any one of claims 1 to 5, which comprises the following steps: 1-1) Mix polyacrylamide with water to obtain an aqueous polyacrylamide solution; 2-1) Mix weathered coal with the aqueous polyacrylamide solution to obtain a dispersion; 3-1) Mix the dispersion with a betaine-type surfactant to obtain the foaming dispersion; or 1-2) Mix polyacrylamide with water to obtain an aqueous polyacrylamide solution; 2-2) Mix a betaine-type surfactant with the aqueous polyacrylamide solution to obtain an aqueous polyacrylamide-betaine solution; 3-2) Mix the aqueous polyacrylamide-betaine solution with weathered coal to obtain the foaming dispersion.
7. The method according to claim 6, characterized in that in step 1-1) or step 1-2), stir at 600 to 1000 rpm for 30 to 45 min to mix evenly.
8. The method according to claim 6, characterized in that in step 2-1) or step 3-2), first stir at 800 to 1000 rpm for 20 to 30 min to mix evenly, and then perform ultrasonic treatment for 5 to 10 min for dispersion mixing.
9. The method according to claim 6, characterized in that in step 3-1) or step 2-2), stir at 400 to 600 rpm for 5 to 10 min for mixing.
10. Application of the foaming dispersion according to any one of claims 1 to 5 or the foaming dispersion prepared by the method according to any one of claims 6 to 9 in displacing the oil stored in the fractures and / or within the cavities of a high salinity fractured-vuggy reservoir; Preferably, the application is in displacing the oil stored in the fractures and / or within the cavities of a high salinity salt rock formation and / or a high salinity fractured-vuggy reservoir caused by sedimentation; Preferably, the application is for displacing the shallow layer of high salinity marine sedimentary rock formation and / or the oil stored in the fractures and / or within the vugs of the high temperature and high salinity fracture-vug reservoir caused by marine sedimentation; Preferably, the upper limit of the salinity is 21×10 4 mg / L.
Citation Information
Patent Citations
Method for preparing water-soluble high molecular dispersion liquid in cationoid
CN101003601A
Foam generating agent for wet dust removal
CN104629686A
Environment-friendly high-temperature-resistant salt-resistant weathered-coal anti-collapse agent for drilling
CN113322051A
Site soil heavy metal passivator and preparation method thereof
CN114276816A
Temperature-resistant and salt-resistant foaming agent and preparation method thereof
CN114656942A